Misalignment of interest: An actor-network analysis of a government budgeting practice - Abeysinghe, Chandrasiri (Asian Journal of Accounting Perspectives, 2021)
Research aim: This paper aims at finding an explanation as to why a government budget operates as a ritual, as has been observed in the Sri Lankan Government budgeting practice and many Less Developed Country (LDC) accounting studies. Design/ Methodology/ Approach: Designed to be a historical study, this study illustrates the government budgeting practice referring to the Sri Lanka Railway Department (SLRD), benefitting from Actor-Network Theory (ANT) using data from archival sources, content analysis of documents, published materials and interviews. Research finding: This research finds that accounting and control practices dysfunction when they do not support the aligned interests of the underlying actor-network. Theoretical contribution/ Originality: This paper focuses on the ‘aligned interest’ of an actor-network, tracking changes of human and non-human actors of a ruling network over three ruling regimes within 1815 to 2019, illuminating the use of ANT in analysing how accounting practices develop over time. Practitioner/ Policy implication: This research reveals to practitioners in the LDC context, a reason for budgeting to operate as a ritual, helping them to formulate necessary action. To the policymaker, this research reveals that for successful performance, the overall policy framework must address the underlying dominant interest. Research limitation: This research focuses on a single aligned interest in an actor-network. However, some public sector institutions operate with multiple interests. Further studies are needed to understand how accounting and control practices in such a context. Keywords: Government budgeting, Actor-Network Theory, Colonial legacies in accounting, LDC accounting and controls, Political interest in public sector accounting Type of article: Research paper JEL Classification: H61, H72, H83, M48 Received: 3 May 2020 Revised: 6 September 2020, 1 October 2020 Accepted: 9 October 2020 Published online: 29 January 2021